Modulation of the photodynamic activity of a cinnamoyl-coumarin–RGD peptide conjugate via cucurbit[8]uril supramolecular assembly - Benjamín Zúñiga; Paula S. Rivero-Jerez; Sofia Pérez-Del Pino; Francisco Bravo-Cabezas; Francisco Mura; Pablo Barrias; Claudio Acuña-Castillo; Mario A. Faúndez; Alexis Aspeé; Daniel Zúñiga-Núñez; Denis Fuentealba (Journal of Photochemistry and Photobiology B: Biology, 2026)

Reconstructing ocean-atmosphere interactions in La Guajira upwelling system through organic and mineral proxies over the past 1800 years - Aura María Rodriguez-Burgos; Francisco Javier Briceño-Zuluaga; Heitor Evangelista; Valentina Flores-Aqueveque; Juliana Nogueira; Alexis Castillo; William Esteban Quiroga-Camargo; Mercedes Mendez-Millan; Abdelfettah Sifeddine (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Historical activity (1522–2025) of the Masaya volcano in Nicaragua and characterization of Pelé's hair and tears from the 2016 eruption - Guillermo E. Alvarado-Induni; Hugo Delgado-Granados; Martha Navarro-Collado; Arnoldo Castillo-Ferrufino; María Martínez-Cruz; Ariadna Calderón; Carlos Linares-López; Reinaldo Pereira-Reyes; Alexis Debut; Virginia Tenorio; Theofilos Toulkeridis (Journal of South American Earth Sciences, 2026)

Consideration of Abies cilicica for central European reforestation - Ulf Büntgen; Alper Kaan Kadioglu; Kasia Charcinska; Edurne Martinez del Castillo; Alexis Arizpe; Tatiana Bebchuk; Jan Esper; Mirek Trnka; Clive Oppenheimer; Nesibe Köse; Ünal Akkemik; Hüseyin Tuncay Güner (Forest Ecology and Management, 2025)

How do the BRICS approach sustainable concerns? A systematic literature review - Cleiton Hluszko; Diego Alexis Ramos Huarachi; Micaela Ines Castillo Ulloa; Rodrigo Salvador; Fabio Neves Puglieri; Antonio Carlos de Francisco (Environmental Development, 2024)

Colostrum in cheese milk: Effects on physicochemical and microbiological characteristics of milk, whey and fresh cheese - Davinia Sánchez-Macías; Byron Herrera-Chávez; Luci Quevedo-Barreto; Alexis Maldonado-Bonifaz; Álex González-Castillo; Antonio José Trujillo Mesa (International Dairy Journal, 2024)

Regional assessment of the historical trends of mercury in sediment cores from Wider Caribbean coastal environments - Yoelvis Bolaños-Alvarez; Ana Carolina Ruiz-Fernández; Joan-Albert Sanchez-Cabeza; Misael Díaz Asencio; Luisa F. Espinosa; Juan Pablo Parra; Jesús Garay; Ramón Delanoy; Nicolás Solares; Katia Montenegro; Alexis Peña; Fabiola López; et al. (Science of The Total Environment, 2024)

Aspergillosis in a colony of Humboldt penguins (Spheniscus humboldti) in a french zoological park: evaluation of environmental exposure - Tristan Bralet; Veronica Risco-Castillo; Isabel Valsecchi; Sylvie Laidebeure; Anaïs Sailler; Alexis Lécu; Françoise Botterel; Jacques Guillot; Pascal Arné; Grégory Jouvion (Veterinary Research Communications, 2024)

Metal(loid)s content in Concholepas concholepas (Mollusca) and human health assessment in a coastal environmental sacrifice zone, central Chile (∼32°S) - Alexis Castillo; Jorge Valdés; Yery Marambio; Luis Figueroa; Jaime Letelier; Francisco Carcamo (Marine Pollution Bulletin, 2023)

Oxidative conditions along the continental shelf of the Southeast Pacific during the last two millennia: a multiproxy interpretation of the oxygen minimum zone variability from sedimentary records - Praxedes Muñoz; Alexis Castillo; Jorge Valdés; Boris Dewitte (Frontiers in Marine Science, 2023)
The oxygen minimum zone (OMZ) is an essential feature along the Pacific margin, extensively studied for its influence on benthic fauna, acquiring relevance in coastal zones due to its impact on aquaculture species, marine-managed areas, and marine-protected areas. The most evident temporal variability beyond seasonal timescales observed for the OMZ was related to inter-annual variability associated with El Niño, when warmer and more oxygenated waters arrive at shallower zones and the OMZ becomes deeper. However, the impact of oxygen-deficient water that appears sporadically over the shelf is not yet understood. This study provides an integrated view of the oceanographic and climatic conditions behind bottom oxygen conditions along the Chilean continental margin, considering the temporal variability in the South East (SE) Pacific during the last ~2000 years. We organized the information on redox-sensitive metals and δ 15 N from sedimentary cores obtained from shelf zones from 23°S to 36°S at water depths lower than 100 m. The results demonstrate the variability in the upper part of the OMZ over the shelf, which seems to respond to climatic oscillations. The element distribution indicated in particular a more intense OMZ was developed over the shelf before 1400 AD, followed by more oxygenated bottom conditions afterward, except between 1925 and 1970 off 36°S when the OMZ was intensified, a condition that was not observed at the northern sites. This period mostly coincided with a low Pacific Decadal Oscillation amplitude and reduced El Niño Southern Oscillation (ENSO) activity. In the last 50 years, the proxy data suggests less intense suboxic environment along the Chilean margin. This weakening of the upper boundary of the OMZ in the last decades is interpreted as resulting from the accumulative effect of ventilation processes at different time scales.

Metal(oid)s content in High-Andean aquatic systems of the Atacama Desert, Chile: environmental assessment of extreme ecosystems - Jorge Valdés; Yery Marambio-Alfaro; Alexis Castillo; Marcos Guiñez; Oliver Cooper (Environmental Science and Pollution Research, 2022)

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Seasonality in marine ecosystems: Peruvian seabirds, anchovy, and oceanographic conditions - Giannina Passuni; Christophe Barbraud; Alexis Chaigneau; Hervé Demarcq; Jesus Ledesma; Arnaud Bertrand; Ramiro Castillo; Angel Perea; Julio Mori; Vincent A. Viblanc; Jose Torres‐Maita; Sophie Bertrand (Ecology, 2016)
In fluctuating environments, matching breeding timing to periods of high resource availability is crucial for the fitness of many vertebrate species, and may have major consequences on population health. Yet, our understanding of the proximate environmental cues driving seasonal breeding is limited. This is particularly the case in marine ecosystems, where key environmental factors and prey abundance and availability are seldom quantified. The Northern Humboldt Current System ( NHCS ) is a highly productive, low‐latitude ecosystem of moderate seasonality. In this ecosystem, three tropical seabird species (the Guanay Cormorant Phalacrocorax bougainvillii , the Peruvian Booby Sula variegata , and the Peruvian Pelican Pelecanus thagus ) live in sympatry and prey almost exclusively on anchovy, Engraulis ringens . From January 2003 to December 2012, we monitored 31 breeding sites along the Peruvian coast to investigate the breeding cycle of these species. We tested for relationships between breeding timing, oceanographic conditions, and prey availability using occupancy models. We found that all three seabird species exhibited seasonal breeding patterns, with marked interspecific differences. Whereas breeding mainly started during the austral winter/early spring and ended in summer/early fall, this pattern was stronger in boobies and pelicans than in cormorants. Breeding onset mainly occurred when upwelling was intense but ecosystem productivity was below its annual maxima, and when anchovy were less available and in poor physiological condition. Conversely, the abundance and availability of anchovy improved during chick rearing and peaked around the time of fledging. These results suggest that breeding timing is adjusted so that fledging may occur under optimal environmental conditions, rather than being constrained by nutritional requirements during egg laying. Adjusting breeding time so that fledglings meet optimal conditions at independence is unique compared with other upwelling ecosystems and could be explained by the relatively high abundances of anchovy occurring throughout the year in the NHCS .

Axonal regeneration after spinal cord injury in zebrafish and mammals: differences, similarities, translation - Katarina Vajn; Jeffery A. Plunkett; Alexis Tapanes-Castillo; Martin Oudega (Neuroscience Bulletin, 2013)